Childhood and Adolescents Sleep Bruxism Treatment: A Systematic Review - Jordana Senff; Danielle Veiga Bonotto; Priscila Brenner Hilgenberg-Sydney; Aline Sebastiani; Rafaela Scariot; Lisa Yurie Oda (Sleep Science)
Introduction Sleep Bruxism (SB) is a common condition in childhood that can cause multiple consequences such as abnormal tooth wear, tensional headaches, masticatory muscle pain, or fatigue. The literature reports some interventions, however the treatment for SB in children is not well-established.